2011
DOI: 10.1074/jbc.m111.267641
|View full text |Cite
|
Sign up to set email alerts
|

Short Hairpin RNA Screen Indicates That Klotho Beta/FGF19 Protein Overcomes Stasis in Human Colonic Epithelial Cells

Abstract: Normal human colonic epithelial cells (HCECs) are not immortalized by telomerase alone but also require CDK4. Some human cell types growth-arrest due to stress-or aberrant signaling-induced senescence (stasis). Stasis represents the consequences of growth conditions culture that are inadequate to maintain long-term proliferation. Overexpressed CDK4 titers out p16 and allows cells to ignore the growth arrest signals produced by stasis. To identify factors contributing to the inadequate culture environment, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…FGF19‐deficient mice show reduced hepatocyte proliferation because of impaired cell cycle progression . The activation of FGF19 signalling contributes to maintaining long‐term proliferation and immortalization of colonic epithelial cells . FGF19 stimulates the proliferation and survival of retinal pigment epithelial cells, which exerts a neuroprotective effect .…”
Section: Discussionmentioning
confidence: 99%
“…FGF19‐deficient mice show reduced hepatocyte proliferation because of impaired cell cycle progression . The activation of FGF19 signalling contributes to maintaining long‐term proliferation and immortalization of colonic epithelial cells . FGF19 stimulates the proliferation and survival of retinal pigment epithelial cells, which exerts a neuroprotective effect .…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Klothoγ (KLG) or LCLT has been implicated in immortalization of normal human colonic epithelial cells 92 . Reversibly, this means that overexpression/up-regulation of LCLT would not immortalize the colonic cells.…”
Section: Dicationmentioning
confidence: 99%
“…Reversibly, this means that overexpression/up-regulation of LCLT would not immortalize the colonic cells. Kim et al 92 show that the KLG/LCTL knockdown lead to disappearance of KLA (Klothoα) which is a tumor suppressor and canonical Wnt antagonist. In colorectal cancer, LCLT might be highly regulated and after the ETC-1922159 administration, the LCLT was found to be downregulated.…”
Section: Dicationmentioning
confidence: 99%
“…The KL family comprises of three proteins, α-Klotho (KLA), β-Klotho (KLB), and γ-Klotho (KLG). KLs act as cofactors of fibroblast growth factors (FGFs)19, 21 and 23 (7)(8)(9). The FGF pathway performs a vital role in various stages of cancer development, including mitogenesis, cell differentiation, and angiogenesis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between KLG and cancer progression remains unclear. Currently, there are very few reports on the association between KLG and cancer (9,23,24). One study reported that KLA enhances the activity of chemotherapeutic drugs on pancreatic cancer cells (25).…”
Section: Introductionmentioning
confidence: 99%